Exploring Non Fungible Tokens in the Digital Economy: Stakeholders, Ecosystem, Risks, and Opportunity - Basry, Mas'ud; Prayogo, Imam (Journal Economic Business Innovation, 2024)
Purpose: In this research, we analyze what essentially drives the Non-Fungible Token (NFT) market, namely, NFT adoption, investor participation, content creator, technological infrastructure, market value and speculation.Method: A quantitative research approach was adopted, employing the blockchain transaction data, NFT marketplace indices, and investor behavior analysis. Hypotheses testing and relationships between variables were performed using descriptive and inferential statistical techniques, including regression models.Findings: The results indicate that NFT adoption has a positive effect on market utility and a negative effect on market value. A high level of participation amongst investors correlates with a stable market, whereas speculation causes price fluctuations. The behavior of content creators is considered a driving factor on the market, while technological infrastructure is important to improve efficiency in the market.Novelty: This study is a novel combination of blockchain performance metrics with market value and investor participation. It builds on the existing literature by examining the phenomenon of content creators and technological elements behind market success.Implications: For investors, content creators and platform developers, the findings have practical implications. Strategies based on these insights can help mitigate market risks, enhance market stability, and foster sustainable growth in the NFT ecosystem.